2018
DOI: 10.18699/vj18.372
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of Leaf Pathogens of Common Spring Wheat in the West Asian Regions of Russia and North Kazakhstan in 2017

Abstract: Листовые болезни яровой пшеницы-бурая ржавчина (возбудитель-Puccinia triticina), желтая пятнистость (пиренофороз) (Pyrenophora tritici-repentis) и темно-бурая пятнистость (Сochliobolus sativus = Bipolaris sorokiniana)-относятся к группе распространенных и потенциально опасных болезней в западноазиатских регионах России и Северном Казахстане. Для обоснования стратегий генетической защиты пшеницы необходимы популяционные исследования фитопатогенов. Цель работыхарактеристика структуры популяций возбудителей бурой… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 8 publications
0
16
0
3
Order By: Relevance
“…Nevertheless, it is clear that the phytopathological situation in the region is fundamentally different from other regions of Russia, where the protective effect of the Lr19 gene is overcome. Currently, virulence to Lr19 is registered in many Russian regions where varieties with this gene are cultivated [ 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is clear that the phytopathological situation in the region is fundamentally different from other regions of Russia, where the protective effect of the Lr19 gene is overcome. Currently, virulence to Lr19 is registered in many Russian regions where varieties with this gene are cultivated [ 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors revealed a diversity in the virulence of isolates: in Russia, 4 races of P. tritici-repentis (1, 2, 4, and 8), and in Kazakhstan -five races (1, 3, 4, 6, and 8) were identified. Study of the population structure of P. tritici-repentis in the West Asian regions of Russia and North Kazakhstan showed that a high degree of similarity in the structure of fungi populations from these regions was noted on the basis of toxin formation, which indicates a single epidemiological zone (Gultyaeva et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…in Sorokin, and Drechslera sorokiniana (Sacc.) Subramanian & Jain, causes diseases on a number of cereals, including wheat ( Tunali et al., 2008 ; Devi et al., 2018 ; Gultyaeva et al., 2018 ; Gupta et al., 2018b ; Jamil et al., 2018 ; Singh et al., 2019 ; Villa-Rodríguez et al., 2019 ; Li et al., 2020 ). The teleomorph for this fungus is Cochliobolus sativus (Ito & Kuribayashi) Drechs.…”
Section: Bipolaris Sorokinianamentioning
confidence: 99%
“…Spot blotch is a common disease on wheat in all continents ( Duveiller et al., 1998 ; Al-Saadi et al., 2002 ; Neupane et al., 2010 ; Al-Sadi, 2016 ; Devi et al., 2018 ; Gultyaeva et al., 2018 ; Gupta et al., 2018a ; Gupta et al., 2018b ). Losses due to spot blotch are high, especially in warmer areas of the world.…”
Section: Spot Blotchmentioning
confidence: 99%